Membangun Karakter Peserta Didik Melalui Kesantunan Berbahasa - Fajar Kurniadi; Hilda Hilaliyah; Sangaji Niken Hapsari (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2018)
Language is a self-reflection. The more polite the language is used, reflects politely in thought and action. However, polite and polite language in action is not easy to apply, especially for those who are still at an early age. This is also supported by the abundance of language use in the educational environment. The habit of using polite language should start early and need the maximum support from various environments, including the educational environment. The community service activities are done by growing the language-friendly culture in the school by doing counseling.The purpose of this activity is to provide understanding and understanding of the citizens of the school importance of language politeness. By using polite language, the learning climate in the school will be conducive to focus on the learning objectives, one of which is character education. This activity is a problem solving as well as an alternative to create a peaceful learning environment and support teaching and learning activities. The characters that can be trained with the use of polite language are faithful and devoted, tolerance, love the homeland, discipline, cooperation, solidarity, honesty, exemplary, and love the truth.  Kata Kunci: Pendidikan Karakter; Kesantunan Berbahasa.